A claus sulfur recovery catalyst containing acid gas and a method of making

CN122999290APending Publication Date: 2026-10-30JIANGSU TIANDONG NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611397084.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-09
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0006]为了克服上述背景技术中现有克劳斯硫磺回收催化剂存在的抗硫沉积性能差、耐水热稳定性不足以及对COS、CS2有机硫组分转化效率较低的问题,本发明的目的在于提供一种含酸性气体的克劳斯硫磺回收催化剂及制备方法

Benefits of technology

本发明通过单宁酸与苯硼酸之间形成动态硼酸酯键结构,可在催化剂表面构建具有可逆调节能力的活性界面,使含硫中间体在催化表面的迁移与吸附过程更加稳定,有助于降低局部硫富集造成的硫沉积现象;同时,正硅酸乙酯水解形成的硅氧网络能够对动态硼酸酯结构进行限域固定,提高催化剂孔结构稳定性及耐水热性能,降低高温高湿条件下的孔道塌陷风险。进一步地,本发明引入四氰基乙烯作为强吸电子型有机小分子,可调节催化剂表面电子云分布,增强对COS、CS2等有机硫组分的活化能力,提高硫中间体转化效率,并促进硫物种快速脱附,从而有效提高催化剂的硫回收效率、抗硫酸盐沉积能力及长期运行稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122999290A_ABST
    Figure CN122999290A_ABST
Patent Text Reader

Abstract

The application discloses a kind of acid gas-containing claus sulfur recovery catalyst and preparation method, belong to sulfur recovery catalytic material technical field.The catalyst includes synergic modified carrier, tetracyanoethylene, active alumina, titanium dioxide, iron oxide, cerium oxide, pore structure regulator, anti-sulfur deposition additive, binder and forming aid;The synergic modified carrier is the composite structure formed by tannic acid, phenylboric acid and tetraethyl orthosilicate by dynamic borate ester bond-silicon oxygen network synergic modification.The stable active interface is synergically constructed by dynamic borate ester structure and silicon oxygen network, and the surface electron distribution of catalyst is adjusted using tetracyanoethylene, which can effectively improve the sulfur recovery efficiency, reduce the sulfur deposition rate, and at the same time, enhance the water and heat stable performance of catalyst and the conversion capacity of COS, CS2 organic sulfur components.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of sulfur recovery catalytic materials technology, and in particular to a Claus sulfur recovery catalyst containing acidic gas and its preparation method. Background Technology

[0002] The Claus sulfur recovery process is a crucial technology for treating high-sulfur gases in the petroleum refining, natural gas purification, coal chemical, and coking industries. It primarily utilizes a combination of thermal and catalytic reactions to convert hydrogen sulfide in acidic gases into elemental sulfur, thereby reducing sulfur emissions and recovering sulfur resources. With the increasing demand for treating high-sulfur crude oil, sulfur-containing natural gas, and complex industrial waste gases, Claus sulfur recovery units place higher demands on the low-temperature activity, sulfur deposition resistance, and hydrothermal stability of catalysts.

[0003] Currently, commonly used Claus sulfur recovery catalysts mainly consist of activated alumina, titanium dioxide, and composite metal oxides. While they can achieve a certain degree of sulfur recovery, several problems remain in actual operation. Firstly, in high-humidity, high-sulfur vapor environments, sulfur deposits and sulfate coatings easily form on the catalyst surface, obscuring active sites and thus reducing catalytic activity. Secondly, the pore structure of existing catalysts has poor stability, easily leading to pore collapse and a decrease in specific surface area under long-term high-temperature hydrothermal conditions, affecting the diffusion and conversion efficiency of sulfur-containing intermediates. Furthermore, the conversion efficiency of traditional catalysts for organic sulfur components such as COS and CS2 in acidic gases is relatively limited, making it difficult to meet the application requirements of deep sulfur recovery processes.

[0004] In existing technologies, some studies have modified catalysts with alkali metals, rare earth oxides, or silicon oxides to improve catalyst stability and sulfur resistance. However, most modification methods still rely on single physical loading or ordinary chemical doping, lacking synergistic structures that can stably regulate the migration of sulfur intermediates and surface electron distribution, resulting in limited improvement in the overall performance of the catalyst. Furthermore, there is a lack of research on the synergistic regulation of dynamic confinement structures and electron acceptor-type organic small molecules in existing modification systems, making it difficult to simultaneously achieve resistance to sulfur deposition, hydrothermal resistance, and the conversion capacity of complex sulfur-containing components.

[0005] Therefore, developing a novel synergistically modified Claus sulfur recovery catalyst with improved conversion efficiency of sulfur intermediates and enhanced resistance to sulfur deposition is of significant research importance and industrial application value. Summary of the Invention

[0006] To overcome the problems of poor sulfur deposition resistance, insufficient hydrothermal stability, and low conversion efficiency of COS and CS2 organic sulfur components in existing Claus sulfur recovery catalysts mentioned above, the present invention aims to provide a Claus sulfur recovery catalyst containing acidic gases and its preparation method. The present invention employs a dynamic borate ester bond-silica confined synergistic modification structure to regulate the catalyst support interface. A dynamic association structure is formed between tannic acid and phenylboronic acid, and a stable silica-oxygen network is constructed by combining tetracyanoethylene as an electron acceptor organic molecule. Simultaneously, tetracyanoethylene is introduced as an electron acceptor type organic small molecule to enhance the catalyst surface electron migration ability and the activation ability of sulfur-containing intermediates. Furthermore, a highly stable composite catalytic system is formed by combining activated alumina, titanium dioxide, iron oxide, and cerium oxide. The present invention can effectively improve the conversion efficiency of the catalyst for complex sulfur-containing components, reduce the sulfur deposition rate, and enhance the long-term stability of the catalyst in high-temperature, high-humidity acidic gas environments.

[0007] The objective of this invention can be achieved through the following technical solutions: A Claus sulfur recovery catalyst containing acidic gases comprises the following raw materials in parts by weight: 80-160 parts of a synergistic modified support; 2-15 parts of tetracyanoethylene; 20-80 parts of activated alumina; 10-50 parts of titanium dioxide; 2-20 parts of iron oxide; 1-15 parts of cerium oxide; 3-20 parts of a pore structure modifier; 2-15 parts of an anti-sulfur deposition aid; 5-25 parts of a binder; and 1-10 parts of a molding aid. The synergistic modified support is a composite structure formed by the synergistic modification of tannic acid, phenylboronic acid, and tetraethyl orthosilicate through dynamic borate ester bond-silica confinement.

[0008] Optionally, the synergistic modification carrier comprises the following raw materials in parts by weight: 10-40 parts tannic acid; 5-25 parts phenylboronic acid; 10-35 parts tetraethyl orthosilicate; 20-80 parts ethanol; and 20-100 parts deionized water.

[0009] Optionally, the preparation method of the synergistically modified support includes the following steps: (1) Add tannic acid to a mixed solution of ethanol and deionized water and stir to dissolve it. Then add phenylboronic acid to carry out a mixed reaction, so that the phenolic hydroxyl group in tannic acid and phenylboronic acid can undergo dynamic association to obtain a pre-complexed solution. (2) Add tetraethyl orthosilicate to the pre-complexed solution and carry out hydrolysis and polycondensation reaction under stirring conditions to gradually form a silicon-oxygen network, while confining the dynamic borate ester structure inside the silicon-oxygen framework to obtain a synergistic modified sol. (3) The synergistic modified sol is aged, dried and pulverized to obtain the synergistic modified carrier.

[0010] Optionally, the stirring and dissolving temperature in step (1) is 25-50°C, the stirring time is 1-3 hours, and the reaction time after the addition of phenylboronic acid is 1-4 hours.

[0011] Optionally, in step (2), the tetraethyl orthosilicate is added for 20 to 60 minutes, the hydrolysis and polycondensation reaction temperature is 40 to 80°C, and the reaction time is 2 to 6 hours.

[0012] Optionally, the aging time in step (3) is 6 to 24 hours, the drying temperature is 60 to 120°C, and the drying time is 4 to 12 hours.

[0013] Optionally, the pore structure modifier is a mixture of boehmite and polyethylene glycol in a mass ratio of (2-6):(1-3); the anti-sulfur deposition aid is a mixture of magnesium oxide and aluminum phosphate in a mass ratio of (1-4):(1-2); the binder is a mixture of pseudo-monohydrate alumina and silica sol in a mass ratio of (3-8):(1-4); and the molding aid is a mixture of methylcellulose and stearic acid in a mass ratio of (2-5):(1-2).

[0014] Optionally, a method for preparing a Claus sulfur recovery catalyst containing acidic gas includes the following steps: S1, the synergistic modified carrier, activated alumina, titanium dioxide and iron oxide are added to a mixing device for premixing to obtain composite powder; S2, tetracyanoethylene, cerium oxide, pore structure regulator and anti-sulfur deposition aid are added to the composite powder and dispersed and mixed at high speed. Then binder and molding aid are added and kneaded to obtain catalyst mixture. S3, the catalyst mixture is extruded, dried and calcined to obtain Claus sulfur recovery catalyst containing acidic gas.

[0015] Optionally, the premixing speed in step S1 is 300-800 rpm, and the premixing time is 20-60 min; the high-speed dispersion speed in step S2 is 1500-4000 rpm, the dispersion time is 30-120 min, and the kneading time is 1-4 h.

[0016] Optionally, the drying temperature in step S3 is 80–140°C, the drying time is 4–10 h, the calcination temperature is 450–750°C, and the calcination time is 2–8 h.

[0017] The beneficial effects of this invention are: This invention utilizes a dynamic borate ester bond structure formed between tannic acid and phenylboronic acid to construct an active interface with reversible adjustment capabilities on the catalyst surface. This stabilizes the migration and adsorption processes of sulfur-containing intermediates on the catalyst surface, helping to reduce sulfur deposition caused by local sulfur enrichment. Simultaneously, the silicon-oxygen network formed by the hydrolysis of tetraethyl orthosilicate can confine and fix the dynamic borate ester structure, improving the stability of the catalyst's pore structure and hydrothermal resistance, and reducing the risk of pore collapse under high temperature and humidity conditions. Furthermore, this invention introduces tetracyanoethylene as a strongly electron-withdrawing organic molecule, which can adjust the electron cloud distribution on the catalyst surface, enhance the activation ability of organic sulfur components such as COS and CS2, improve the conversion efficiency of sulfur intermediates, and promote rapid desorption of sulfur species. This effectively improves the catalyst's sulfur recovery efficiency, resistance to sulfate deposition, and long-term operational stability. Attached Figure Description

[0018] The invention will now be further described with reference to the accompanying drawings.

[0019] Figure 1 The infrared spectra of the synergistic modification of the support by tannic acid and dynamic borate ester bond-siloxane confinement are compared. Detailed Implementation

[0020] The present invention will be further described below with reference to specific embodiments. However, the present invention is not limited to the following embodiments. Equivalent adjustments made without departing from the spirit and essence of the present invention should also be considered to fall within the protection scope of the present invention.

[0021] Example 1: The purpose of this example is to obtain a Claus sulfur recovery catalyst containing acidic gas with high pore structure stability and basic sulfur recovery performance.

[0022] S1, 10 parts of tannic acid were added to a mixed solution of 20 parts ethanol and 20 parts deionized water, and stirred at 300 rpm for 1 hour at 25°C to ensure complete dissolution. Then, 5 parts of phenylboronic acid were added and the reaction continued for 1 hour to allow the phenolic hydroxyl groups in the tannic acid to undergo dynamic association with the phenylboronic acid, resulting in a pre-complexed solution. Subsequently, 10 parts of tetraethyl orthosilicate were added dropwise over 20 minutes, and a hydrolysis-condensation reaction was carried out at 40°C for 2 hours to obtain a synergistically modified sol. After aging the synergistically modified sol for 6 hours, it was dried at 60°C for 4 hours and then pulverized to obtain a synergistically modified carrier. S2, 80 parts of the synergistic modified carrier, 20 parts of activated alumina, 10 parts of titanium dioxide and 2 parts of iron oxide were added to a mixing device and premixed at 300 rpm for 20 min to obtain a composite powder; then 2 parts of tetracyanoethylene, 1 part of cerium oxide, 3 parts of pore structure regulator and 2 parts of anti-sulfur deposition aid were added to the composite powder and dispersed at 1500 rpm for 30 min; then 5 parts of binder and 1 part of molding aid were added and kneaded for 1 h to obtain a catalyst mixture. S3, the catalyst mixture is extruded into strips, then dried at 80°C for 4 hours, and then calcined at 450°C for 2 hours to obtain Claus sulfur recovery catalyst containing acidic gas.

[0023] Example 2: The purpose of this example is to obtain a Claus sulfur recovery catalyst containing acidic gases with optimal overall performance in terms of sulfur recovery efficiency, anti-sulfur deposition properties, and hydrothermal stability.

[0024] S1, 25 parts of tannic acid were added to a mixed solution of 50 parts ethanol and 60 parts deionized water, and stirred at 550 rpm for 2 hours at 38°C to ensure complete dissolution. Then, 15 parts of phenylboronic acid were added and the reaction continued for 2 hours to allow the phenolic hydroxyl groups in the tannic acid to form a dynamic borate ester association structure with the phenylboronic acid, resulting in a pre-complexed solution. Subsequently, 22 parts of tetraethyl orthosilicate were added dropwise over 40 minutes, and a hydrolysis-condensation reaction was carried out at 60°C for 4 hours to obtain a synergistically modified sol. After aging the synergistically modified sol for 12 hours, it was dried at 90°C for 8 hours and then pulverized to obtain a synergistically modified carrier. Figure 1 Infrared spectral comparisons show that the modified tannic acid-phenylboronic acid-tetraethyl orthosilicate synergistic modified support exhibits high performance at 3385 cm⁻¹. -1 The nearby OH absorption peak was significantly weakened and shifted, indicating that a dynamic association occurred between the phenolic hydroxyl group in tannic acid and phenylboronic acid; at 1290 cm⁻¹ -1 and 1045~1080cm -1 The presence of a significant enhancement peak nearby indicates the formation of a BOC and Si-O-Si synergistic structure; simultaneously, at 960 cm⁻¹... -1 and 800cm -1 The presence of newly added characteristic peaks nearby indicates that the silicon-oxygen network was successfully constructed; the results show that a stable dynamic borate ester bond-silicon-oxygen confinement synergistic modification structure was formed between tannic acid, phenylboronic acid and tetraethyl orthosilicate. S2, 120 parts of the synergistic modified carrier, 50 parts of activated alumina, 30 parts of titanium dioxide and 10 parts of iron oxide were added to a mixing device and premixed at 550 rpm for 40 min to obtain a composite powder; then 8 parts of tetracyanoethylene, 8 parts of cerium oxide, 10 parts of pore structure regulator and 8 parts of anti-sulfur deposition aid were added to the composite powder and dispersed at high speed at 2800 rpm for 80 min; then 15 parts of binder and 5 parts of molding aid were added and kneaded for 2 h to obtain a catalyst mixture. S3, the catalyst mixture is extruded into strips, then dried at 110°C for 7 hours, and then calcined at 620°C for 5 hours to obtain Claus sulfur recovery catalyst containing acidic gas.

[0025] Example 3: The purpose of this example is to obtain a Claus sulfur recovery catalyst containing acidic gas with high high temperature resistance and resistance to sulfate deposition.

[0026] S1. 40 parts of tannic acid were added to a mixed solution of 80 parts ethanol and 100 parts deionized water. The solution was stirred at 800 rpm for 3 hours at 50°C until fully dissolved. Then, 25 parts of phenylboronic acid were added and the reaction continued for 4 hours to allow the phenolic hydroxyl groups in the tannic acid to form a dynamic association structure with the phenylboronic acid, resulting in a pre-complexed solution. Subsequently, 35 parts of tetraethyl orthosilicate were added dropwise over 60 minutes, and a hydrolysis-condensation reaction was carried out at 80°C for 6 hours to obtain a synergistically modified sol. After aging the synergistically modified sol for 24 hours, it was dried at 120°C for 12 hours and then pulverized to obtain a synergistically modified carrier. S2, 160 parts of the synergistic modified carrier, 80 parts of activated alumina, 50 parts of titanium dioxide and 20 parts of iron oxide were added to a mixing device and premixed at 800 rpm for 60 min to obtain a composite powder; then 15 parts of tetracyanoethylene, 15 parts of cerium oxide, 20 parts of pore structure regulator and 15 parts of anti-sulfur deposition aid were added to the composite powder and dispersed at 4000 rpm for 120 min; then 25 parts of binder and 10 parts of molding aid were added and kneaded for 4 h to obtain a catalyst mixture. S3, the catalyst mixture is extruded into strips, then dried at 140°C for 10 hours, and then calcined at 750°C for 8 hours to obtain Claus sulfur recovery catalyst containing acidic gas.

[0027] Comparative Example 1: The purpose of this comparative example is to verify the influence of the dynamic borate ester synergistic structure on the sulfur recovery performance and anti-sulfur deposition performance of the catalyst.

[0028] S1, 25 parts of tannic acid were added to a mixed solution of 50 parts ethanol and 60 parts deionized water, and stirred at 550 rpm for 2 hours at 38°C to ensure complete dissolution. Then, 22 parts of tetraethyl orthosilicate were added dropwise over 40 minutes, and a hydrolysis-condensation reaction was carried out at 60°C for 4 hours to obtain a modified sol. After aging the modified sol for 12 hours, it was dried at 90°C for 8 hours and then pulverized to obtain a single silicon-oxygen modified carrier. S2, 120 parts of a single silicon-oxygen modified carrier, 50 parts of activated alumina, 30 parts of titanium dioxide and 10 parts of iron oxide were added to a mixing device and premixed at 550 rpm for 40 min to obtain a composite powder; then 8 parts of tetracyanoethylene, 8 parts of cerium oxide, 10 parts of pore structure regulator and 8 parts of anti-sulfur deposition aid were added to the composite powder and dispersed at high speed at 2800 rpm for 80 min; then 15 parts of binder and 5 parts of molding aid were added and kneaded for 2 h to obtain a catalyst mixture. S3, the catalyst mixture is extruded into strips, then dried at 110°C for 7 hours, and then calcined at 620°C for 5 hours to obtain the Claus sulfur recovery catalyst.

[0029] Comparative Example 2: The purpose of this comparative example is to verify the influence of the silicon-oxygen confined structure on the stability of the catalyst pore structure and its hydrothermal resistance.

[0030] S1, 25 parts of tannic acid were added to a mixed solution of 50 parts of ethanol and 60 parts of deionized water, and stirred at 550 rpm for 2 hours at 38°C to ensure complete dissolution. Then, 15 parts of phenylboronic acid were added and the reaction continued for 2 hours to allow the phenolic hydroxyl groups in the tannic acid to form a dynamic association structure with the phenylboronic acid, thus obtaining a pre-complexed solution. After that, without adding tetraethyl orthosilicate, the pre-complexed solution was directly aged for 12 hours and dried at 90°C for 8 hours. The solution was then pulverized to obtain a dynamic borate ester modified carrier. S2, 120 parts of dynamic borate ester modified carrier, 50 parts of activated alumina, 30 parts of titanium dioxide and 10 parts of iron oxide were added to a mixing device and premixed at 550 rpm for 40 min to obtain composite powder; then 8 parts of tetracyanoethylene, 8 parts of cerium oxide, 10 parts of pore structure regulator and 8 parts of anti-sulfur deposition aid were added to the composite powder and dispersed at high speed at 2800 rpm for 80 min; then 15 parts of binder and 5 parts of molding aid were added and kneaded for 2 h to obtain catalyst mixture. S3, the catalyst mixture is extruded into strips, then dried at 110°C for 7 hours, and then calcined at 620°C for 5 hours to obtain the Claus sulfur recovery catalyst.

[0031] Comparative Example 3: The purpose of this comparative example is to verify the effect of tetracyanoethylene organic small molecules on the conversion ability of catalyst sulfur intermediates and the anti-sulfur deposition performance.

[0032] S1, 25 parts of tannic acid were added to a mixed solution of 50 parts ethanol and 60 parts deionized water, and stirred at 550 rpm for 2 hours at 38°C to ensure complete dissolution. Then, 15 parts of phenylboronic acid were added and the reaction continued for 2 hours to allow the phenolic hydroxyl groups in the tannic acid to form a dynamic borate ester association structure with the phenylboronic acid, resulting in a pre-complexed solution. Subsequently, 22 parts of tetraethyl orthosilicate were added dropwise over 40 minutes, and a hydrolysis-condensation reaction was carried out at 60°C for 4 hours to obtain a synergistically modified sol. After aging the synergistically modified sol for 12 hours, it was dried at 90°C for 8 hours and then pulverized to obtain a synergistically modified carrier. S2, 120 parts of the synergistic modified carrier, 50 parts of activated alumina, 30 parts of titanium dioxide and 10 parts of iron oxide were added to a mixing device and premixed at 550 rpm for 40 min to obtain a composite powder; then 8 parts of cerium oxide, 10 parts of pore structure regulator and 8 parts of anti-sulfur deposition aid were added to the composite powder and dispersed at high speed at 2800 rpm for 80 min; then 15 parts of binder and 5 parts of molding aid were added and kneaded for 2 h to obtain a catalyst mixture. S3, the catalyst mixture is extruded into strips, then dried at 110°C for 7 hours, and then calcined at 620°C for 5 hours to obtain the Claus sulfur recovery catalyst.

[0033] Performance testing: 1. Test methods for sulfur recovery and conversion performance The Claus sulfur recovery catalysts prepared in the examples and comparative examples were loaded into a fixed-bed reactor at a loading volume of 20 mL. Before reaction, the catalysts were pretreated at 300°C for 2 h under a nitrogen atmosphere. Subsequently, a simulated acidic gas was introduced, containing 1.2% H2S, 0.6% SO2, 15% water vapor, and the remainder nitrogen. The total gas flow rate was controlled at 1000 mL / min, and the reaction temperature was 280°C. After continuous reaction for 8 h, the H2S and SO2 contents in the outlet gas were measured, and the sulfur recovery conversion rate was calculated.

[0034] 2. Test method for resistance to sulfur deposition The Claus sulfur recovery catalysts prepared in the examples and comparative examples were subjected to continuous sulfur deposition experiments in a simulated reaction environment containing high-sulfur vapor. The reaction gas contained 2.0% H2S, 1.0% SO2, 20% water vapor, and the remainder nitrogen. The reaction temperature was controlled at 320°C, and the reaction was carried out continuously for 24 hours. After the test, the catalyst was weighed, and the amount of sulfur deposited per unit mass of catalyst surface was calculated. The catalyst activity retention rate was also recorded to evaluate the catalyst's resistance to sulfur deposition.

[0035] 3. Test method for water and thermal stability performance The Claus sulfur recovery catalysts prepared in the examples and comparative examples were placed in a high-temperature hydrothermal aging apparatus and continuously treated at 650°C for 12 hours in a nitrogen atmosphere containing 20% ​​water vapor, and then cooled to room temperature. The aged catalysts were then reloaded into a fixed-bed reactor and their performance was tested under the same sulfur recovery reaction conditions. The hydrothermal stability of the catalysts was evaluated by the change in sulfur recovery conversion rate before and after aging.

[0036] 4. Test methods for organic sulfur conversion performance The Claus sulfur recovery catalysts prepared in the examples and comparative examples were packed into a fixed-bed reactor. A simulated acidic gas containing COS and CS2 was introduced at 300°C, wherein the volume fraction of COS was 0.3%, the volume fraction of CS2 was 0.2%, the volume fraction of H2S was 1.0%, the volume fraction of water vapor was 10%, and the remainder was nitrogen. The total gas flow rate was controlled at 800 mL / min. After continuous reaction for 6 h, the residual content of COS and CS2 in the outlet gas was detected, and the conversion rate was calculated to evaluate the catalyst's ability to deeply convert organic sulfur components.

[0037] Table 1 Performance Test Results According to Table 1, the Claus sulfur recovery catalysts containing acidic gases prepared in Examples 1-3 are significantly better than the comparative examples in terms of sulfur recovery conversion rate, anti-sulfur deposition performance, hydrothermal stability, and COS and CS2 conversion performance. This indicates that the dynamic borate ester bond-silicon-oxygen confined synergistic modification structure and tetracyanoethylene electron acceptor structure constructed in this invention can effectively improve the overall performance of the catalyst.

[0038] In Example 2, the sulfur recovery conversion rate reached 98.7%, significantly higher than that of Comparative Examples 1-3. This indicates that the confined interface formed by the dynamic borate ester structure and the silicon-oxygen network can effectively improve the adsorption and migration efficiency of sulfur intermediates. Simultaneously, tetracyanoethylene regulates the electron cloud distribution on the catalyst surface, promoting the activation reaction of H2S and organic sulfur components, thereby improving the overall sulfur recovery efficiency. In contrast, Comparative Example 1 lacks the dynamic borate ester structure formed by phenylboronic acid, resulting in a lack of a dynamic active interface on the catalyst surface, leading to a decrease in the migration ability of sulfur intermediates and a significant reduction in sulfur recovery efficiency.

[0039] The sulfur deposition test results show that Example 2 had the lowest sulfur deposition, at only 7.9 mg·g⁻¹. -1This indicates that the dynamic borate ester bond structure can alleviate local sulfur enrichment, while the silicon-oxygen confined network helps maintain pore structure stability and promotes rapid desorption of sulfur species, thereby reducing the sulfur deposition rate on the catalyst surface. In contrast, Comparative Example 2, lacking a stable silicon-oxygen network, was more prone to pore blockage and sulfur accumulation during the reaction, resulting in a significantly higher sulfur deposition rate.

[0040] Regarding hydrothermal stability, Example 2 achieved an activity retention rate of 96.8% after high-temperature hydrothermal aging, significantly higher than the comparative examples. This indicates that the silicon-oxygen confined structure effectively enhances the catalyst framework stability and reduces the risk of pore structure collapse under high-temperature and high-humidity conditions. Simultaneously, the dynamic borate ester structure improves interfacial flexibility and stability, thereby enhancing the long-term operational stability of the catalyst. Although Example 3 exhibits high stability, the higher content of some components leads to a decrease in pore diffusion efficiency, resulting in slightly lower overall performance compared to Example 2.

[0041] Example 2 showed a conversion rate of 97.4% for COS and CS2, which was significantly better than that of Comparative Example 3. This indicates that tetracyanoethylene, as a strong electron-withdrawing small organic molecule, can enhance the electron migration ability of the catalyst surface, improve the activation efficiency of organic sulfur molecules, and promote the further conversion of sulfur intermediates. Therefore, it can effectively improve the deep sulfur recovery capability in complex acidic gas systems.

[0042] In summary, this invention, through the synergistic effect of dynamic borate bond structure, silicon-oxygen confinement network, and tetracyanoethylene electron acceptor structure, can significantly improve the sulfur recovery efficiency, anti-sulfur deposition performance, hydrothermal stability, and organic sulfur conversion capacity of Claus sulfur recovery catalyst, and has good prospects for industrial application.

Claims

1. A Claus sulfur recovery catalyst containing acidic gas, characterized in that, The Claus sulfur recovery catalyst containing acidic gas comprises the following raw materials in parts by weight: 80-160 parts of synergistic modified support; 2-15 parts of tetracyanoethylene; 20-80 parts of activated alumina; 10-50 parts of titanium dioxide; 2-20 parts of iron oxide; 1-15 parts of cerium oxide; 3-20 parts of pore structure regulator; 2-15 parts of anti-sulfur deposition aid; 5-25 parts of binder; and 1-10 parts of molding aid. The synergistic modified support is a composite structure formed by the synergistic modification of tannic acid, phenylboronic acid, and tetraethyl orthosilicate through dynamic borate ester bond-silica confinement.

2. The Claus sulfur recovery catalyst containing acidic gas according to claim 1, characterized in that, The synergistic modified carrier comprises the following raw materials in parts by weight: 10-40 parts tannic acid; 5-25 parts phenylboronic acid; 10-35 parts tetraethyl orthosilicate; 20-80 parts ethanol; and 20-100 parts deionized water.

3. A Claus sulfur recovery catalyst containing acidic gas according to claim 1 or 2, characterized in that, The preparation method of the synergistic modified carrier includes the following steps: (1) Add tannic acid to a mixed solution of ethanol and deionized water and stir to dissolve it. Then add phenylboronic acid to carry out a mixed reaction, so that the phenolic hydroxyl group in tannic acid and phenylboronic acid can undergo dynamic association to obtain a pre-complexed solution. (2) Add tetraethyl orthosilicate to the pre-complexed solution and carry out hydrolysis and polycondensation reaction under stirring conditions to gradually form a silicon-oxygen network, while confining the dynamic borate ester structure inside the silicon-oxygen framework to obtain a synergistic modified sol. (3) The synergistic modified sol is aged, dried and pulverized to obtain the synergistic modified carrier.

4. The Claus sulfur recovery catalyst containing acidic gas according to claim 3, characterized in that, The stirring and dissolving temperature in step (1) is 25-50℃, the stirring time is 1-3h, and the reaction time after the addition of phenylboronic acid is 1-4h.

5. The Claus sulfur recovery catalyst containing acidic gas according to claim 3, characterized in that, In step (2), the tetraethyl orthosilicate is added over a period of 20 to 60 minutes, the hydrolysis and polycondensation reaction temperature is 40 to 80°C, and the reaction time is 2 to 6 hours.

6. The Claus sulfur recovery catalyst containing acidic gas according to claim 3, characterized in that, The aging time in step (3) is 6 to 24 hours, the drying temperature is 60 to 120°C, and the drying time is 4 to 12 hours.

7. The Claus sulfur recovery catalyst containing acidic gas according to claim 1, characterized in that, The pore structure modifier is a mixture of boehmite and polyethylene glycol in a mass ratio of (2-6):(1-3); the anti-sulfur deposition aid is a mixture of magnesium oxide and aluminum phosphate in a mass ratio of (1-4):(1-2); the binder is a mixture of pseudo-monohydrate alumina and silica sol in a mass ratio of (3-8):(1-4); and the molding aid is a mixture of methylcellulose and stearic acid in a mass ratio of (2-5):(1-2).

8. A method for preparing a Claus sulfur recovery catalyst containing acidic gas, characterized in that, The preparation method includes the following steps: S1, the synergistic modified carrier, activated alumina, titanium dioxide and iron oxide are added to a mixing device for premixing to obtain composite powder; S2, tetracyanoethylene, cerium oxide, pore structure regulator and anti-sulfur deposition aid are added to the composite powder and dispersed and mixed at high speed. Then binder and molding aid are added and kneaded to obtain catalyst mixture. S3, the catalyst mixture is extruded, dried and calcined to obtain Claus sulfur recovery catalyst containing acidic gas.

9. The method for preparing a Claus sulfur recovery catalyst containing acidic gas according to claim 8, characterized in that, In step S1, the premixing speed is 300-800 rpm and the premixing time is 20-60 min; in step S2, the high-speed dispersion speed is 1500-4000 rpm, the dispersion time is 30-120 min, and the kneading time is 1-4 h.

10. The method for preparing a Claus sulfur recovery catalyst containing acidic gas according to claim 8, characterized in that, The drying temperature in step S3 is 80-140℃, the drying time is 4-10h, the calcination temperature is 450-750℃, and the calcination time is 2-8h.